2022
DOI: 10.1021/acsomega.1c06046
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Based on Peripheral Blood Mononuclear Cells to Dissect the Mechanisms of Chaigui Granules for Treating Depression

Abstract: Chaigui granules were a traditional Chinese medicine (TCM) preparation with antidepressant effects derived from a famous antidepressant prescription. It was of great significance to clarify the antidepressant mechanism of Chaigui granules for the clinical application of this drug. In this study, a chronic unpredictable mild stress (CUMS) depression model was successfully established, and behavioral indicators were used to evaluate the antidepressant effect. Second, the CD4+, CD8+, and CD4+/CD8+ levels were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…[ 45 ] PTGS2 encodes COX-2, a rate-limiting enzyme for the arachidonic acid metabolism of prostaglandins, its expression increases in response to cerebral ischemia, which promotes inflammatory responses and exacerbates neurological damage in the brain. [ 46 ] Stigmasterol can down-regulate PTGS2 expression by inhibiting the NF-κB pathway, which can promote cell proliferation, migration, and angiogenesis, and reduce inflammation and cell apoptosis, thereby decreasing neural damage after cerebral ischemia. [ 47 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 45 ] PTGS2 encodes COX-2, a rate-limiting enzyme for the arachidonic acid metabolism of prostaglandins, its expression increases in response to cerebral ischemia, which promotes inflammatory responses and exacerbates neurological damage in the brain. [ 46 ] Stigmasterol can down-regulate PTGS2 expression by inhibiting the NF-κB pathway, which can promote cell proliferation, migration, and angiogenesis, and reduce inflammation and cell apoptosis, thereby decreasing neural damage after cerebral ischemia. [ 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…[45] PTGS2 encodes COX-2, a rate-limiting enzyme for the arachidonic acid metabolism of prostaglandins, its expression increases in response to cerebral ischemia, which promotes inflammatory responses and exacerbates neurological damage in the brain. [46] Stigmasterol can down-regulate PTGS2 expression by inhibiting the NF-κB pathway, which can promote cell proliferation, migration, and angiogenesis, and reduce inflammation and cell apoptosis, thereby decreasing neural damage after cerebral ischemia. [47] GO enrichment analysis revealed that NV is mainly involved in BP such as the acetylcholine receptor signaling pathway, cellular response to acetylcholine, postsynaptic signal transduction, serotonin receptor signaling pathway, and neurotransmitter receptor activity.…”
Section: Mol/herb Id Component Name Degreementioning
confidence: 99%
“…L-isoleucine, sebacic acid, and allantoin were identified as potential pharmacodynamic biomarkers related to the efficacy of this TCM. Similarly, LC-MS-based metabolomics of peripheral blood mononuclear cells (PBMCs) was used to investigate the antidepressant mechanism of Chaigui granules [115]. Their antidepressant effects were attributed to improved immune function and regulation of the purine metabolic pathway in PBMCs.…”
Section: Traditional Chinese Medicinesmentioning
confidence: 99%